Chinese Language Policy and Uyghur Youth: Examining Language Policies and Language Ideologies. Issue 3 (4th May 2021) - Han, Yawen; Cassels Johnson, David
ABSTRACT: This article examines the connections between educational language policy for Uyghur youth and the language ideologies among Uyghur families. Chinese language policy has historically accommodated multilingualism, and promoted minoritized language education; however, we reveal how policies have shifted towards favoring and promoting Putonghua (only) as the lingua franca. We then present interview data collected from four Uyghur youth attending university, all of whom are the targets of Uyghur language policy in China. In many ways, Chinese language policy has had the desired effect on these students. We provide a historical overview of educational language policy in China, with a focus on its impact on Uyghur speakers, and then illuminate how language attitudes and ideologies circulate through official policy texts, among families, and among students.